Scholarly activities in hospitality and tourism higher education among private higher institutions in Australia - Edmund Goh (Laureate Education Inc, 2013)
The purpose of this paper is to explore the notion of scholarship and develop research and scholarship strategies among Private Higher Institutions delivering Tourism and Hospitality degree programs in Australia. In doing so, this paper confronts the traditional view of research publications as the only form of scholarship by traditional universities. This paper argues that the purpose of scholarship should be focused towards improving a teacher's teaching and learning process. These new knowledge need not be limited through peer reviewed journals only, but can be achieved through less formal means of communication such as fieldtrips to industry and attending conferences. This paper utilizes the six Scholarship key points as defined on P. 19 of the National Protocols for Higher Education Approval Processes in Australia by MCEETYA  to investigate methods to capture scholarship beyond traditional research publications. DOI: 10.18870/hlrc.v3i2.108